2014
DOI: 10.1136/bmjspcare-2013-000578
|View full text |Cite
|
Sign up to set email alerts
|

Variations in specialist palliative care referrals: findings from a population-based patient cohort of acute myeloid leukaemia, diffuse large B-cell lymphoma and myeloma

Abstract: ObjectiveTo develop and implement a methodology for capturing complete haematological malignancy pathway data and use it to identify variations in specialist palliative care (SPC) referrals.MethodsIn our established UK population-based patient cohort, 323 patients were diagnosed with acute myeloid leukaemia, diffuse large B-cell lymphoma or myeloma between May 2005 and April 2008, and died before April 2010. A day-by-day calendar approach was devised to collect pathway data, including SPC referrals, to supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 34 publications
0
30
1
Order By: Relevance
“…MM is an example of an incurable haematological cancer in which, due to improvements in therapy, patients now live a comparably long time of 5–10 yr with their disease. New developments warrant insights into long‐term toxicities and better patient management and care, especially towards the end of life . In 1996, a position statement was issued to advocate good symptom management, improving functioning and HRQOL alongside survival as the goal of effective cancer treatment .…”
Section: Discussionmentioning
confidence: 99%
“…MM is an example of an incurable haematological cancer in which, due to improvements in therapy, patients now live a comparably long time of 5–10 yr with their disease. New developments warrant insights into long‐term toxicities and better patient management and care, especially towards the end of life . In 1996, a position statement was issued to advocate good symptom management, improving functioning and HRQOL alongside survival as the goal of effective cancer treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective studies, describing their experiences with different models of integrated SPC in daily clinical practice in patients with HM, report rates of 30-50% of patients who had at least 1 referral to SPC [16,20,21]. SPC seems to be more frequent in patients dying at home and with a longer course of disease, but is not dependent on age or gender [20,21].…”
Section: Experiences With Palliative Carementioning
confidence: 99%
“…SPC seems to be more frequent in patients dying at home and with a longer course of disease, but is not dependent on age or gender [20,21]. A retrospective study in older patients with AML demonstrated that psychosocial support was part of SPC in all patients, hospice in-patient care in 30%, palliative homecare in 61%, treatment in a palliative care outpatient clinic in 14%, and bereavement care in 93% of patients [16].…”
Section: Experiences With Palliative Carementioning
confidence: 99%
“…Howell et al recently demonstrated that referral to palliative care is significantly higher among patients with multiple myeloma than among patients with other hematologic malignancies (odds ratio, 1.96; 95% CI, 1.15 to 3.35). 31 Although relatively small in size and limited to the United Kingdom, this study illustrates contemporary approaches to disease and palliative measures in this patient population. Finally, while it is appealing to posit that therapeutic advances account for the findings of our study, studies with experimental designs with ESRD as primary outcome would be required for confirmation.…”
mentioning
confidence: 95%